Women's leadership in Islam: an analysis on the Hadith "a nation can never prosper if it places woman in its highest public office" - Abdullah, Ismail (s.n, 2012)
The issue of woman's leadership has a political importance and is related to the sociopolitical scene and cultural traditional in some state. we shall therefore focus on political focus on political situation that encompassed women's leadership role in the past and the present. This directed to the different interpretation of hadith throughout the ages and gave precise meaning to every single word of hadith